2021
DOI: 10.4314/rjsshb.v2i1.2
|View full text |Cite
|
Sign up to set email alerts
|

Capital structure and financial sustainability of Microfinance Institutions (MFIs) in Rwanda

Abstract: The aim of this study was to assess the effect of capital structure on financial sustainability of microfinance institutions (MFIs), and find out the extent to which capital structure affects financial sustainability of MFIs in Rwanda. Data was collected from annual financial reports of MFIs and SACCOs for the period 2014-2018. Due to data availability, only a panel of 20 MFIs and SACCOs was considered using fixed effects OLS regression models. Findings from this study reveal that the use of debt as financing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
0
0
Order By: Relevance
“…Este enfoque resultó ser el más adecuado para el análisis de las variables determinantes de la estructura de capital. De acuerdo con Rutanga et al (2021), al igual que en la regresión lineal simple, los coeficientes rotados revelan el cambio en la magnitud de la variable dependiente por cada incremento unitario en la variable explicativa correspondiente. Estos coeficientes, por tanto, se presentan en sus respectivas unidades de medida.…”
Section: Procesamiento De Informaciónunclassified
“…Este enfoque resultó ser el más adecuado para el análisis de las variables determinantes de la estructura de capital. De acuerdo con Rutanga et al (2021), al igual que en la regresión lineal simple, los coeficientes rotados revelan el cambio en la magnitud de la variable dependiente por cada incremento unitario en la variable explicativa correspondiente. Estos coeficientes, por tanto, se presentan en sus respectivas unidades de medida.…”
Section: Procesamiento De Informaciónunclassified
“…It is identified during the sector that microfinance governance (CG) has turned out to be one of the vital problems in comparing the strengths and functions of a company (3). According to Rutanga et al (18), despite the fact that although MFIs exist in many developing nations, millions of families and individuals still lack access to loans and other financial services. This is because the microfinance organization has higher operating and capital costs, which makes it difficult to meet client demand and help them achieve their financial and social goals.…”
Section: Problem Statementmentioning
confidence: 99%
“…Also, microfinance banks must have sufficient liquidity to repay their debt obligations. Rutanga et al (18) determined the impact of capital structure on MFIs' financial viability and found out the amount to which capital structure moves. Data were gathered from a panel of 20 MFIs' annual financial reports.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, although some studies have reported a positive relationship between deposits and operational self‐sufficiency (Abrar & Javaid, 2016; Aza, 2018; Bayai & Ikhide, 2018; Duguma & Han, 2018; Fadikpe et al, 2022), others have found a negative relationship (Bibi et al, 2022; Bogan, 2012; Dorfleitner et al, 2020; Gul et al, 2017). Similarly, conclusions regarding the influence of equity on financial self‐sufficiency (FSS) have also been divided, with some studies suggesting a positive impact (Abdulhakim & Mersha, 2020; Nyamsogoro, 2016; Rutanga et al, 2021; Sekabira, 2013), whereas others challenge this assertion (Ali et al, 2020; Mwizarubi et al, 2016; Perera, 2021; Quayes, 2012).…”
Section: Introductionmentioning
confidence: 99%